UMPSA expands cooperation with Libya through partnerships with LYAPS and LASR - Nur Ezzati, Mohd Nasir (UMPSA, 2024)
KUALA LUMPUR, 7 May 2024 — In a strategic move to expand its global academic and research network, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) participated in a meeting with representatives from the Libyan Ministry of Higher Education and Scientific Research (MoHESR).